The structure of the Narrative Place in Biography of Sheikh Mohammed Bin Rashid: My story As Pattern - Alkharji, Najeya (Al-Adab Journal, 2023)
Interest in autobiography emerged as an independent narrative genre at the end of the nineteenth century, which made it technically qualified for analysis according to the latest narrative theories.              The biography of Sheikh Mohammed Bin Rashid is subjected to this analytical study, to reveal the structure of the narrative place therein, as the study revealed six spatial axes presented by the text, which are: types of places, when multiple types of places appeared that formed this axis, such as: the private place, and the place The closed, and the geometrical place... The second axis presented the significance of the place, such as: significance, expressiveness, symbolic significance, and functional significance.              Through the third axis, the research presented the functions of the place, where the functional roles played by the place were revealed. Such as the cognitive role, the educational role, and the critical role, within the external functions of the place, contributing to the consolidation of human relations, and revealing the feelings of personalities within the internal functions of the place.              The fourth axis showed the relationship between space and time, to emphasize the inseparability of the relationship between them by revealing how space and time relate.              The fifth axis identified the place and its relationship to the description when it dealt with the aesthetics of the narrative place in the biography by highlighting the descriptive images of the place, which contributed to revealing the political, historical, social, and economic contents of the place. This increases the reader's connection to the text.              Thus, the importance of the sixth axis emerged in emphasizing the extent of the role played by the place in the text's completion by linking the six axes included in the study.